PENGARUH TEKANAN DAN UKURAN PARTIKEL TERHADAP KUALITAS BRIKET ARANG CANGKANG COKLAT - Lina Lestari; Erzam S. Hasan; Risna Risna (Jurnal Aplikasi Fisika, 2017)
The purpose of this research is to know the pressurized and particle size influence on Cacao’s shell charcoal briquette making. It is made from cacao as an adhesive with the ratio of 9:1. The used particle sizes are 60 mesh, 70 mesh, 80 mesh, and 100 mesh. Sample is formed in molded cylinder with the diameter of 4 cm with the centered hole of 0,8 cm and the compacted pressure is 34,66 kg/cm2, 69,32 kg/cm2, 103,98 kg/cm2. It’s test is density, water level, activation time, flame velocity, the highest temperature, the time needed for the highest temperature, and the shifting of burning temperature. The result shows that the best briquette quality is the one with particle size 80 mesh and it’s highest temperature is 464,4oC on compacted 103,98 kg/cm2. The difference of each briquette particle size shows the tendency of increasing on it’s activation time and it’s flame velocity.Keywords : Briquette, cacao shell, pressure, particle size.